Evaluation of two commercial IBR marker vaccines against Bubaline alphaherpesvirus 1 in water buffalo (Bubalus bubalis) - Cappelli, Giovanna; Petrini, Stefano; Grandoni, Francesco; Grassi, Carlo; De Donato, Immacolata; Signorelli, Federica; Napolitano, Francesco; Vecchio, Roberta; Balestrieri, Anna; De Carlo, Esterina; De Matteis, Giovanna; Martucciello, Alessandra (Frontiers in Veterinary Science, 2025)
The present study aimed to evaluate two commercial infectious bovine rhinotracheitis (IBR) marker vaccines against Bubaline alphaherpesvirus 1 (BuAHV-1) in water buffalo (Bubalus bubalis). Thirteen water buffaloes seronegative to Bovine alphaherpesvirus 1 (BoAHV-1) and BuAHV-1 were selected and divided into three groups (VAX-1, VAX-2, CNT). VAX-1 received an IBR marker (gE-/tk-) live vaccine; VAX-2 received an IBR marker (gE-) inactivated vaccine; CNT represented the controls. Two injections of 2 mL each were administered 21 days apart. On 55 post-vaccination days (PVDs), all animals were challenged infected with wild-type BuAHV-1. Nasal swabs and serum samples were collected at different experimental times and were used for virological, serological and immunological investigations. After seven post-challenge days (PCDs), only the CNT evidenced nasal mucus discharge and increased rectal temperature. The glycoprotein B (gB) of BoAHV-1 positivity was detected using Real-time PCR from PCDs 2 to 7 in vaccinated groups. In the controls, gB positivity was detected from PCD 2 to 15. On PVD 34, all vaccinated animals progressively increased their neutralizing antibody (NA) titers statistically until the end of the experiments. In the controls, the NAs appeared on PCD 10. Flow cytometric analysis of lymphocyte populations revealed that BuAHV-1 activates adaptive immune responses. Throughout the entire examination period, both vaccinated and unvaccinated animals exhibited similar trends. However, significant differences were observed at specific time points in the CD4+, CD8+, and γδ T lymphocyte subsets between the vaccinated groups and control group. These findings suggested that the IBR marker vaccines tested in this study could be used to protect the water buffalo against BuAHV-1.